Issues in health and health care related to race/ethnicity, immigration, SES and gender - Kronenfeld, Jennie J. (Bingley, U.K. : Emerald, 2012)
The 30th Anniversary volume of Research in the Sociology of Health Care looks at the important links between major social factors and health and health care. The four main factors examined in the book are race/ethnicity, immigration, Socioeconomic Status (SES) and gender. Starting with an introductory chapter which reviews some of the important sociological literature on these social factors as linked to health, the book goes on to cover various key issues, including obesity, ageing, immigration and racial segregation.
Health care system issues and race/ethnicity, immigration, SES and gender as sociological issues linking to health and health care / Jennie Jacobs Kronenfeld -- Obesity in Mexican-American adults : interplay of immigrant generation, gender, and socioeconomic status / Igor Ryabov -- Delayed diagnosis of tuberculosis in the U.S.-Mexico border region : a health narratives approach / Angélica Forero-Quintana, Sara E. Grineski -- Views of Japanese immigrant women about care as they age / Atsuko Kawakami, Jennie Jacobs Kronenfeld -- Two sides of the Potomac : a qualitative exploration of immigrant families' health care experiences in Virginia and Washington, DC / Colleen K. Vesely, Marriam Ewaida, Katina B. Kearney -- Ethnicity and the use of 'accepted' and 'rejected' complementary/alternative medical therapies in Canada : evidence from the Canadian community health survey / Christopher J. Fries -- Racial residential segregation and access to health-care coverage : a multilevel analysis / Kathryn Freeman Anderson, Andrew S. Fullerton -- Gendering affective disorders in direct-to-consumer advertisements / Jennifer Arney, Rose Weitz -- 'More than boobs and ovaries' : BRCA positive young women and the negotiation of medicalization in an online message board / Elena Frank -- Close-calls that older homebound women handled without help while alone at home / Eileen J. Porter, Melinda S. Markham -- Countervailing influences of black and women legislators on state age friendliness / Jean Giles-Sims, Joanne Connor Green, Charles Lockhart -- Intersectional identities and worker experiences in home health care : the national home health aide survey / Carter Rakovski, Kim Price-Glynn.
Print version record
Keywords: Health & Fitness -- Health Care Issues; Social Science -- Sociology -- General; Medical -- Health Care Delivery; Health systems & services; Sociology; Social medicine; Minorities -- Medical care; Medical care